Vibronic Effects Analysis of the Substituent Effect on the Spectral Properties of the EMI and CPL of Three [7]Helicene Derivatives - Qiushuang Xu; Meishan Wang; Yanli Liu (Molecules)
The substituent effect has a significant influence on the optical properties of spectral shape, width, and wavelength, and the intensities of the maximum peaks of emission (EMI) and circularly polarized luminescence (CPL). In this work, we conducted a systematic theoretical study to investigate how substituents alter the optical response in the EMI and CPL spectra of three [7]helicene derivatives at the vibronic level. To incorporate the vibronic effect, a state-of-the-art time-dependent (TD) method was used to achieve the fully converged spectra. In the meantime, a time-independent (TI) approach also provided a way to show the progression of the spectra, serving as a complementary strategy and creating reliable documentation for the experiment. The experimental spectra of EMI and CPL are nicely reproduced, which validates the reliability of the Adiabatic Hessian (AH) model in simulating experimental data. This allowed us to analyze in detail the effect of substituents, particularly on the optical responses. The introduction of cyano and methoxy groups is highlighted, as they altered the transition dipole moments and led to a 1000-fold increase in the intensity of EMI and CPL. Moreover, substituents can also rationally alter the spectral shape of EMI and CPL by affecting the responsible normal modes. The unique CN stretching and the MeO rotation in the substituted [7]helicene are highlighted as key factors contributing to the different behaviors of EMI and CPL. This sheds light on the design and synthesis of helicenes that can serve as ideal full-color EMI and CPL emitters.